Strategi entrepreneur cerdas: Mengenali risiko dan bertahan di tengah disrupsi - Istiyadah, Narulita Al Kholifina (Maliki Interdisciplinary Journal, 2025)
The development of digital technology and easy access to information have encouraged entrepreneurial growth, but also created new challenges such as market disruption, changing consumer behavior, and business uncertainty. This study aims to analyze the strategies used by digital entrepreneurs to manage business risks amid disruption. Using a descriptive qualitative method and case study approach, data were collected through literature review. The findings show that strategies such as product diversification, service digitalization, and the use of online platforms are essential for adapting to market changes. Common risks include customer loss, obsolete technology, and shifting consumer preferences. Risk management plays a central role in strategic decision-making and business resilience. Key success factors identified are rapid adaptation, continuous innovation, and data-driven risk mitigation. The study concludes that risk management is a vital pillar for entrepreneurs in facing digital disruption and ensuring future business continuity and growth.